2010
DOI: 10.1177/1352458510384011
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the established non-MHC multiple sclerosis loci in an Indian population

Abstract: Although the power of this study was limited, our preliminary data suggest that disease susceptibility genes in MS in the Indian population may be similar to those of western populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
42
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(46 citation statements)
references
References 20 publications
(12 reference statements)
4
42
0
Order By: Relevance
“…In a study of this size and considering 96 variants, we would anticipate seeing up to five apparently reversed effects by chance alone. A similar low frequency of apparently reversed signals was seen in our previous African American study (Isobe et al, 2013) and also in our study of European multiple sclerosis variants in an Indian data set (Pandit et al, 2011). Although such allele flipping could theoretically have resulted from unusual population-based differences in allele frequencies (Lin et al, 2007;Zaykin and Shibata, 2008;Clarke and Cardon, 2010), no such differences are apparent in the 1000 Genomes data set (The 1000 Genomes Project Consortium, 2010), where the minor allele for these four SNPs is the same in both populations.…”
Section: à5supporting
confidence: 83%
“…In a study of this size and considering 96 variants, we would anticipate seeing up to five apparently reversed effects by chance alone. A similar low frequency of apparently reversed signals was seen in our previous African American study (Isobe et al, 2013) and also in our study of European multiple sclerosis variants in an Indian data set (Pandit et al, 2011). Although such allele flipping could theoretically have resulted from unusual population-based differences in allele frequencies (Lin et al, 2007;Zaykin and Shibata, 2008;Clarke and Cardon, 2010), no such differences are apparent in the 1000 Genomes data set (The 1000 Genomes Project Consortium, 2010), where the minor allele for these four SNPs is the same in both populations.…”
Section: à5supporting
confidence: 83%
“…In our previously published study of limited power, CD6 gene associated SNP had shown a trend of association. [16] Our recently published replication study on 110 European risk variants provides evidence that many if not all the MS risk variants identified in populations of European ancestry are likely to also be risk variants in the South Asian population. This study hypothesized that B cells and certain immunoglobulins might play an important role in the pathogenesis of MS in South Asian and other Asian populations in comparison to European MS patients.…”
Section: Discussionmentioning
confidence: 99%
“…SNP genotyping was performed on an ABI7500 real-time polymerase chain reaction (PCR) genotyping platform using predesigned TaqMan SNP genotyping assays (Applied Biosystems Inc., Foster City, CA, USA) as described earlier. [16] In short, 4 μl of normalized genomic DNA (5 ng/ul) was aliquoted to the bottom surface of a MicroAmp ® Optical 96-Well Reaction Plate. The DNA sample was dried down completely by evaporation.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, investigation among them showed that except one study [14], almost all of them suggested that C allele is associated with high risk of MS [7]. IL7Ra rs6897932 SNP is located in exon 6 which encodes integral membrane domain of the receptor, while rs6897932 SNP causes skipping at this site which leads to more soluble form of protein.…”
Section: Discussionmentioning
confidence: 99%